Emerging Micro Manufacturing Technologies and Applications - Tapoglou, Nikolaos (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book is a reprint of the Special Issue Emerging Micro Manufacturing Technologies and Applications that was published in Micromachines. It contains eleven articles, including one Editorial, nine research papers, and one review.